Applications of Generative Artificial Intelligence in Medicine: Opportunities and Ethical Considerations - Sharma, Mohan Raj (Journal of Institute of Medicine Nepal, 2024)
Generative Artificial Intelligence (AI) has emerged as a transformative tool in various domains, including medical sector. Generative AI models like ChatGPT offer unparalleled potential in diagnostics, prognostications, and research assistance. However, their integration necessitates careful scrutiny of risks, including privacy violations and the propagation of inaccuracies. Establishing clear guidelines for their use in academic medicine and research is imperative for the responsible use of these tools. This article explores the foundational concepts of generative AI, highlights its applications in medicine, research, and academia, and addresses ethical and practical concerns.